Who believes what? : exploring the world's major religions - Wills, Anna, 1978- (Owlkids Books, 2018)
"Who believes what: The big book of world religions introduces young readers to the five major religions: Hinduism, Buddhism, Judaism, Christianity, Islam, in a simple, visually engaging book that combines a search-and-find aspect with thoroughly researched information about the histories, places of worship, festivals and celebrations, gods, and religious leaders and more of each major religion. Each religion is introduced in a double-page spread that explores the people, places, rituals and objects associated with it. On the next spread, images from the illustration are pulled out and more detailed information is provided. The illustrations are full of life and will have readers thinking they can hear the sound of voices and music at a celebration or that they can breathe in the smells of the market."--